Material Process: The Participants Analysis in the Jakarta Post Article “All the single, working mothers" - Lilik Damayanti; Elisabeth Milaningrum (UICELL, 2017)
This research employs a Functional Grammar Approach (FGA) and used the method of descriptive which employs clause. This study is qualitative because it focuses on the meanings, concepts, definitions, and descriptions of things. The source data that used in this research is based from the articles which found in jakarta Post.This research focused on how the participant roles for material processes which is classified into several participants, there are: (1) Affected is the participant that someone or something happens to; (2) Recipient is the participant which indicates by indirect object in ditransitive clauses but takes the preposition to rather than for when the indirect object moved to the final; (3) Beneficiary is the participants which also indicates by indirect object in ditransitve clause but takes the preposition for rather than to when the indirect object moved to the final.